Family member engagement with early psychosis specialty care. Issue 5 (9th November 2016) - Lucksted, Alicia; Stevenson, Jennifer; Nossel, Ilana; Drapalski, Amy; Piscitelli, Sarah; Dixon, Lisa B.
Abstract : Background: Family members of individuals with early psychosis (EP) play critical roles in their engagement with EP services, but family member experiences of those roles are insufficiently understood. Methods: We conducted semi‐structured interviews with 18 family members of individuals enrolled in EP services during the Recovery After an Initial Schizophrenia Episode‐Implementation Evaluation Study (RAISE‐IES study), to better understand their experiences engaging with EP specialty care and their roles in client engagement in services. Results: Family members described diverse experiences with the interplay among distress regarding their loved one's illness, uncertainty engaging with programme staff and highly valued facets of the clinical programme. These included ongoing family outreach and support, frequent communication from staff, programme flexibility and individualization of care. They also described varied and stressful complexities involved in providing practical assistance and encouragement to support their loved one's engagement in care. Competing responsibilities, time and resource limitations, and the intricacy of providing support while fostering autonomy impacted their roles and experiences. Conclusions: Given key family roles for most EP clients, understanding family members' highly individual experiences and responding to them in tailored ways is necessary to best support families in helping their loved ones engage in care and recovery as well as navigate their own worry and stress. Recommendations for engaging and supporting family members are highlighted.